2019
DOI: 10.1093/gigascience/giz110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of computational genotyping of structural variation for clinical diagnoses

Abstract: Background Structural variation (SV) plays a pivotal role in genetic disease. The discovery of SVs based on short DNA sequence reads from next-generation DNA sequence methods is error-prone, with low sensitivity and high false discovery rates. These shortcomings can be partially overcome with extensive orthogonal validation methods or use of long reads, but the current cost precludes their application for routine clinical diagnostics. In contrast, SV genotyping of known sites of SV occurrence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
(42 reference statements)
2
40
0
Order By: Relevance
“…5 for SV detection approach). SV genotyping is nontrivial and associated with high uncertainty 33 . Thus, we utilized the multispecies sampling scheme to filter for variants complying with basic population genetic assumptions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 for SV detection approach). SV genotyping is nontrivial and associated with high uncertainty 33 . Thus, we utilized the multispecies sampling scheme to filter for variants complying with basic population genetic assumptions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, our approach led to the discovery of 88 novel deletions and 36 novel inversions when compared to recent genome-wide scans. We note that we also excluded SDs and insertions from our analysis due to difficulties in discovery and subsequent validations using standard short-read genotyping approaches [76]. As improved hybrid-based methods combining long-and short-read data are developed to more accurately identify SVs and their breakpoints, it will be a worthwhile endeavor to return to our dataset to discover additional SVs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sequence resolution is essential for the comparison and genotyping of SVs in many individuals. As these tasks are the basis for association studies and medical diagnosis, efforts should be directed towards a better resolution of the sequence of these variants [8,23]. Results obtained with the local assembly tool MindTheGap showed that the use of the whole read dataset allowed many insertions and even large ones to be assembled.…”
Section: Discussionmentioning
confidence: 99%